Self-exclusion from gambling: A toothless tiger? - Kraus, Ludwig; Loy, Johanna K.; Bickl, Andreas M.; Schwarzkopf, Larissa; Volberg, Rachel A.; Rolando, Sara; Kankainen, Veera E.; Hellman, Matilda; Rossow, Ingeborg; Room, Robin; Norman, Thomas; Cisneros Örnberg, Jenny (Frontiers in Psychiatry, 2022)
While there is evidence for self-exclusion (SE) as an individual-level harm reduction intervention, its effects on reducing harm from gambling at the population level remain unclear. Based on a review of national legal frameworks and SE programs, including their utilization and enforcement in selected high-income societies, the present analysis aims to explore the reach and strengths of SE in the protection of gamblers in these jurisdictions. It places particular emphasis on SE programs’ potential to prevent and minimise gambling harm at the population level. The overview examined SE in Finland, Germany, Italy, Massachusetts (USA), Norway, Sweden, and Victoria (Australia). These jurisdictions differ considerably in how gambling is regulated as well as in how SE is implemented and enforced. The reach and extent of enforcement of SE apparently vary with the polity’s general policy balance between reducing gambling problems and increasing gambling revenue. But in any case, though SE may benefit individual gamblers and those around them, it does not appear to be capable of significantly reducing gambling harm at the population level. To render SE programs an effective measure that prevents gamblers and those linked to them from financial, social, and psychological harm, utilization needs to be substantially increased by reforming legal regulations and exclusion conditions.